2015
DOI: 10.33549/physiolres.932811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fetal Undernutrition and Postnatal Overfeeding on Rat Adipose Tissue and Organ Growth at Early Stages of Postnatal Development

Abstract: Intrauterine and perinatal life are critical periods for programming of cardiometabolic diseases. However, their relative role remains controversial. We aimed to assess, at weaning, sexdependent alterations induced by fetal or postnatal nutritional interventions on key organs for metabolic and cardiovascular control. Fetal undernutrition was induced by dam food restriction (50 % from mid-gestation to delivery) returning to ad libitum throughout lactation (Maternal Undernutrition, MUN, 12 pups/litter). Postnata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…This is a compensatory response to nutrient deficiency in utero which we have previously observed in other organs such as adipose tissue (Muñoz‐Valverde et al . ) and the heart (Rodríguez‐Rodríguez et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…This is a compensatory response to nutrient deficiency in utero which we have previously observed in other organs such as adipose tissue (Muñoz‐Valverde et al . ) and the heart (Rodríguez‐Rodríguez et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in body weight was explained by an increase in body fat mass, at the expense of lean mass 10 . An increase in visceral white adipose tissue is observed at weaning and later in SL rats 8 28 and mice 29 and is accompanied by an increase in adipocyte surface 6 13 30 . However, subcutaneous fat mass is also increased in young but not adult SL mice 31 , indicating that in adulthood, higher body weight and fat mass are mainly due to increased visceral fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data mostly on subjects who were born small for gestational age (SGA) have shown that metabolic abnormalities in adulthood are associated with catch up growth during early life, which also preterm born subjects often experience [ 13 , 14 , 15 , 16 ]. Animal studies [ 17 , 18 ] as well as epidemiological and clinical studies have suggested that early nutritional intake, human examples of which include shorter duration of breastfeeding and higher protein content in infant formula, is associated with cardiometabolic risk factors in later life [ 19 , 20 , 21 ]. Further, early life environment, including maternal diet during pregnancy [ 22 ] and restricted fetal growth [ 23 , 24 ], have been associated with specific food preferences in adult age.…”
Section: Introductionmentioning
confidence: 99%